Constituents and inhibitory effect on human pathogenic bacteria of the roots of Scutellaria baicalensis - Long, Le Duc; Tung, Nguyen Huu; Thom, Nguyen Thi; Choi, Gyung Ja; Hoang, Vu Dinh; Dang, Le Quang (Vietnam Journal of Science and Technology, 2019)
Abstract-HCTN_16Methanol extract of the roots of Scutellaria baicalensis effectively inhibited the bacterial growth of human pathogenic bacteria Staphylococcus aureus ATCC 6538, Bacillus cereus ATCC 21768 and Bacillus subtilis ATCC 6633 at MICs of 2,000 µg/mL. n-Hexane, ethyl acetate and aqueous residues were prepared by successively partitioning the methanol extract with n-hexane and ethyl acetate. Among them, only ethyl acetate layer showed antibiotic effect; whereas n-hexane and aqueous layers were inactive against tested bacteria. The ethyl acetate residue was fractionated by silica gel column chromatography to afford three flavonoids and an oligosaccharide. Their chemical structures were elucidated as wogonin (SB1), baicalein (SB4), baicalin (SB5) and tetrasaccharide (SB10) on the basis of the analysis of NMR and MS spectroscopic data. The isolates were evaluated for in vitro inhibitory effect against human pathogenic bacteria using micro dilution bioassay method. Baicalein (SB4) showed a broad-spectrum inhibition against various human pathogenic bacteria. In particular, it was found to potently inhibit S. aureus ATCC 6538 and B. cereus ATCC 21768 with MICs of 9.5 and 38 µg/mL, respectively. The study results demonstrated antibiotic effect of the extracts from the roots of S. baicalensis and characterization of compounds isolated from the plant materials.